2017
DOI: 10.7860/jcdr/2017/25472.9624
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Evaluation of Enhancement Patterns of Flat Gall Bladder Wall Thickening and Its Correlation with Clinical and Histopathological Findings

Abstract: Introduction: Gall bladder Wall Thickening (GWT) is caused by wide spectrum of diseases. Initially Ultrasound (USG) was used as imaging modality for screening of acute abdomen because of its high sensitivity and real time character. Now, Computed Tomography (CT) is used because of its high temporal and spatial resolution.Aim: Evaluation of GWT and its enhancement patterns on contrast enhanced CT scan in a bid to differentiate benign from malignant causes and to correlate the imaging features with clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Type 3 showed borderline enhancement and thickness of the inner layer with small cystic spaces and non-enhancing outer layer; as seen in adenomyomatosis. Type 4, weakly enhancing thin inner layer and non-enhancing thin outer layer; seen in chronic cholecystitis, and type 5, weakly enhancing thin inner layer and non-enhancing thick outer layer as seen in acute cholecystitis and dengue [16,17]. The sensitivity and specificity of type 1 enhancement pattern on computed tomography for predicting the GB malignancy according to this study were 90.476% and 97.43%, respectively.…”
Section: Iva T4mentioning
confidence: 54%
See 2 more Smart Citations
“…Type 3 showed borderline enhancement and thickness of the inner layer with small cystic spaces and non-enhancing outer layer; as seen in adenomyomatosis. Type 4, weakly enhancing thin inner layer and non-enhancing thin outer layer; seen in chronic cholecystitis, and type 5, weakly enhancing thin inner layer and non-enhancing thick outer layer as seen in acute cholecystitis and dengue [16,17]. The sensitivity and specificity of type 1 enhancement pattern on computed tomography for predicting the GB malignancy according to this study were 90.476% and 97.43%, respectively.…”
Section: Iva T4mentioning
confidence: 54%
“…The sensitivity and specificity of type 1 enhancement pattern on computed tomography for predicting the GB malignancy according to this study were 90.476% and 97.43%, respectively. The positive and negative predictive values were found to be 95% and 95%, respectively [16]. In our previously published study in a region of India endemic for CA GB, we have reported the sensitivity and specificity of MDCT in detection of carcinoma of gall bladder to be 92.8% and 96.7%, respectively [18] ( Table 5).…”
Section: Iva T4mentioning
confidence: 79%
See 1 more Smart Citation
“…However, this pattern may also be seen in cirrhosis and viral hepatitis. 14 The type 5 pattern is depicted by a weakly enhancing, fuzzy, inner layer with a nonenhancing thick outer layer of submucosal oedema, as seen in acute calculous cholecystitis and Dengue fever. 13,14 5.…”
Section: Is the Diffuse Thickening Symmetrical Or Asymmetrical?mentioning
confidence: 99%
“…The sensitivity and specificity of Type 1 enhancement pattern on CT for predicting the Gall Bladder (GB) malignancy were 90.476% and 97.43% respectively, by a study in 2017. 5 The radiologic differential diagnosis includes the more common inflammatory conditions of the gallbladder, benign polyps, xanthogranulomatous cholecystitis, adenomyomatosis, other hepatobiliary malignancies, and metastasis. 6 The study aimed to determine the utility of multi-phase MDCT in the staging and resectability of gallbladder carcinoma.…”
Section: Introductionmentioning
confidence: 99%